Isolated renal intravascular lymphoma: a case report and review of the literature. (August 2014) - Akpinar, Timur Selcuk; Ozkok, Abdullah; Batu, Duygu; Sarihan, Irem; Kose, Murat; Tascioglu, Cemil
Abstract Intravascular large B-cell lymphoma (IVLBCL) is a very rare subtype of extranodal large B-cell lymphoma. It may involve various organ systems such as skin, liver, lung or kidney. Isolated kidney involvement of IVLBCL is also very rare. Herein we report a very rare case of isolated renal IVLBCL presented with fever of unknown origin, acute kidney injury and nephrotic syndrome. Diagnosis was suspected with isolated high renal 18F fluorodeoxyglucose uptake in positron emission tomography and confirmed with renal biopsy. Complete remission was obtained with combined chemotherapy including rituximab. We reviewed the English literature in terms of IVLBCL with renal involvement and we could only find 16 such cases. Accordingly, fever, AKI and nephritic syndrome are the most common presenting symptoms in renal intravascular lymphoma.